Relationship Between Chronobiology And Aging: Adjustments Facing The Technological World - Laura Simões da Costa Pinto; Roberta Almeida Vincenzi; Thais Schaedler; Gabriele Perrut; Fernando Mazzilli Louzada (Geriatrics, Gerontology and Aging)
Although there is no consensus in literature regarding which are the rhythmicity changes that occur during the aging process, it is believed that advanced age may affect the circadian rhythms, leading to a decreased ability to tolerate abrupt phase shift, decreased amplitude of rhythms, phase advance and reduced endogenous period. Therefore, understanding the mechanisms involved in the aging process has become essential for the development of new treatment approaches in order to improve quality of life of the elderly population. The use of technologies has increased over the past years, becoming an important factor to be considered an influence in the circadian rhythms. There is a limited number of studies linking the relationship between sleep-wake cycle and the effect of light and media use in the modern world. Thus, the aim of this review was to analyze the relationship between light, technology, and circadian rhythms in the elderly population.